Lingual Syncretism: Language Features on the Relationship between Tradition and Religion in “Motolobalango” Coronation - Haris Danial; Muhammad Rayyan Kufri (PT. Penerbit Tiga Mutiara, 2023)
In various regions, we often find marriage processions that are guided by customary and Islamic laws that apply as ancestral heritage. Unfortunately, the pattern of syncretism between custom and Islam in marriage is rarely known by society in general. The aim of this research is to describe lingual syncretism in the Motolobalango tradition in Gorontalo. This research is oriented towards qualitative descriptive methods. The results of the research show that the syncretism of Motolobalango marriage customs is indicated in two forms, namely verbal language which appears in five representations of tuja'I speech acts in the form of: greeting, asking for permission, inviting, praising, requesting, and making non-verbal promises to cultural attributes in the form of aato dalalo, tonggu permata, pata potolongito, and yila-yilapito.